Two‐year effectiveness and safety of golimumab in ulcerative colitis: An IG‐IBD study. Issue 1 (1st March 2021) - Pugliese, Daniela; Privitera, Giuseppe; Rogai, Francesca; Variola, Angela; Viola, Anna; Laterza, Lucrezia; Privitera, Antonino C.; Allocca, Mariangela; Bossa, Fabrizio; Cappello, Maria; Daperno, Marco; Lorenzon, Greta; et al.
Abstract: Background: Few data exist regarding the long‐term effectiveness of golimumab in ulcerative colitis. No data have been reported on real‐world continuous clinical response. Objective: This study aimed to describe the long‐term outcomes in a large cohort of patients on golimumab who had ulcerative colitis. Methods: Consecutive patients with active ulcerative colitis, started on golimumab, were enrolled and prospectively followed up. The primary end point was to evaluate the long‐term persistence on golimumab therapy. Results: A total of 173 patients with ulcerative colitis were studied. Of these, 79.2% were steroid dependent, and 46.3% were naïve to anti‐tumour necrosis factor alpha agents. The median duration of golimumab therapy was 52 weeks (range: 4–142 weeks). The cumulative probability of maintaining golimumab treatment was 47.3% and 22.5% at 54 and 108 weeks, respectively. Biological‐naïve status (odds ratio [OR] = 3.02, 95% confidence interval [CI]: 1.44–6.29; p = 0.003) and being able to discontinue steroids at Week 8 (OR = 3.32, 95% CI: 1.34–8.30; p = 0.010) and Week 14 (OR = 2.94, 95% CI: 1.08–8.02; p = 0.036) were associated with longer persistence on therapy. At Week 54, 65/124 (52.4%) postinduction responders were in continuous clinical response. A continuous clinical response was associated with a lower likelihood of golimumab discontinuation throughout the subsequent year of therapy ( p < 0.01). Overall, 40 (23.1%) patients were in clinical remission at the last follow‐up visit. Twenty‐six adverse events were recorded, leading to golimumab withdrawal in 9.2% of patients. Conclusions: : Biological‐naïve status and not requiring steroids at Weeks 8 and 14 seem to be associated with a longer persistence on golimumab therapy in ulcerative colitis.